Screening of metal oxides for Hg0 capture - Zhao, Haitao; Yang, Gang; Pang, Cheng Heng; Fan, Hua; Hall, Philip; Kingman, Sam; Wu, Tao (Elsevier, 2015)
Fossil fuel related industriesare the major anthropogenic sources of Hg0 emission. Due to awareness of the detrimental impact, there is an increasing interest in discovering potential materials for Hg0 removal. In this paper, the first-row transition metals (from V to Zn), Mo and rare earth metals (La and Ce) in the oxidation states supported by γ-Al2O3werepreparedand studied as potential candidates for Hg0 capture. Based on evolution of the parameters of enthalpies (ΔH), Gibbs free energy (ΔG), adsorption peaks (Ta, peak), maximumHg0 capture efficiencies (μmax) and activation energy (Ea)etc, the samples of Cr, Ni, Fe, Mn, Co, Ce and Cu showed better performancesfor Hg0 capture amongst the 11 metal oxides. The results also indicated that MoO3 has potential to promote Hg0 capture since the activation energy is relatively low. Consequently, most of the Mo-based binary metal oxides have relatively high Hg0 removal efficienciescoupled with lowactivation energies. Particularly, the binary metal oxides of CrMo, MnMo, CuMo, CeMo andCoMo could be selected as appropriate candidates for Hg0 capture within specifictemperature windows.